CYBERCRIME (KEJAHATAN BERBASIS KOMPUTER) - Gani, Alcianno (Universitas Dirgantara Marsekal Suryadarma, 2018)
Information technology plays an important role, both in the present and in the future. The Internet is one part of the development of information technology that has opened new horizons in human life. The Internet can be interpreted as an information and communication space that penetrates the boundaries between countries and accelerates the spread of science and simplifies all human activities.However, every positive side must have a negative side. The Internet applies in this case many crimes that can occur in cyberspace called cybercrime. Currently, we cannot feel the word